Whither Management Education? Professional Education, Action Learning and Beyond - Joseph A. Raelin (Management Learning, 1994)
As pedagogical approaches, the professional education model and more recently action learning have each made important contributions to the preparation of experienced students for management practice. Using some carefully chosen domains, these approaches, in particular their advantages and limitations, are reviewed. Some guidelines are then proposed to help develop a future model of management education which in some instances goes beyond even a synthesis of the two extant approaches.
Keywords: I20; I21; O15; M12; M53; 330; Professional education; Action learning; MBA education; Theory and practice